Magnesio-lucchesiite from the Kowary vicinity, Karkonosze Mountains, SW Poland: the third occurrence worldwide. (14th February 2023) - Sęk, Mateusz P.; Włodek, Adam; Stachowicz, Marcin; Woźniak, Krzysztof; Pieczka, Adam
Abstract: Two tourmaline samples occurring in quartz veinlets, which cross-cut an amphibolite body at the Budniki camp near the Kowary town in the south-west part of the Karkonosze Mountains, SW Poland, were studied through microprobe and single crystal X-ray diffraction. Samples were extracted from core and rim regions of crystals with concentric zoning. Chemical and structural data revealed that the core tourmaline is characterised by a dravite–oxy-dravite composition, with the formula: X (Na0.82 Ca0.07 K0.01 Sr0.01 □0.09 )Σ1 Y (Mg1.73 Fe 2+ 0.81 Fe 3+ 0.41 Ti0.04 V0.01 )Σ3 Z (Al5.85 Fe 3+ 0.15 )Σ6 ( T Si6 O18 )(BO3 )3 (OH)3 W (OH0.50 O0.50 )Σ1 and unit cell parameters a = 15.97377(14) Å and c = 7.22644(7) Å. The rim part of the crystals has a magnesio-lucchesiite composition, described by the formula: X (Ca0.49 Na0.41 K0.04 Sr0.02 □0.04 )Σ1 Y (Mg1.87 Fe 2+ 0.95 Ti0.15 Fe 3+ 0.02 V0.02 )Σ3 Z (Al5.49 Fe 3+ 0.51 )Σ6 (BO3 )3 ( T Si6 O18 )(OH)3 W (O0.81 F0.18 OH0.01 )Σ1 with unit cell parameters a = 15.9863(3) Å and c = 7.22426(15) Å. Both tourmalines show similar refined populations at the Y and Z sites: Y [(Fe 2+ 0.810 Mg0.680 )Σ1.490 (Al1.044 Fe 3+ 0.413 V0.009 )Σ1.465 Ti0.045 ]Σ3 Z (Al4.806 Mg1.042 Fe 3+ 0.152 )Σ6 (dravite–oxy-dravite), and Y [(Fe 2+ 0.945 Mg0.750 )Σ1.695 (Al0.737 Fe 3+ 0.404 V0.018 )Σ1.159 Ti0.146 ]Σ3 Z (Al4.749 Mg1.115 Fe 3+ 0.137 )Σ6 (magnesio-lucchesiite), with a comparable Mg/(Mg + Fe) ratio of 0.54–0.56, oxidation of Fe expressed as Fe 3+ /Fetotal ratio 0.36–0.41, and trace components such as Ti, Sr, V, Cr, Ni and Co. The geological history of the eastern Karkonosze region in the Kowary vicinity indicates that both tourmalines crystallised from B-bearing metamorphic fluids mobilised by Variscan prograde metamorphism from the protoliths of the Velká Upá mica schists that host the Budniki amphibolite. The fluids migrated into the tectonised amphibolite enriched in Ti, V, Cr, Ni and Co, and mineralised the fractures within it through deposition of soluble species in the form of quartz–tourmaline veinlets. Magnesio-lucchesiite crystallised in an early retrogression stage, probably from Ca- and F-bearing fluids secondary enriched in B by the dissolution of dravite–oxy-dravite. The Budniki camp is, in addition to the type and co-type magnesio-lucchesiite localities, the third documented occurrence of the species worldwide.